Efektivitas Digitalisasi Pendaftaran Tanah pada Kantor Pertanahan - Putri Rani Margareth Sipahutar; Besty Habeahan (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The development of digital technology has encouraged the government to modernize public services, including in the field of land affairs. Traditionally, land registration has been associated with long, complex procedures that are often prone to abuse of authority. To address these challenges, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has begun implementing a digital-based land registration system. However, its implementation raises an important question: is this digital system truly effective in improving the quality of services at the Land Office, or does it instead create new obstacles? This study aims to analyze the effectiveness of land registration digitalization, particularly in terms of accessibility, efficiency, transparency, and the challenges encountered during its implementation. The research employs an empirical juridical method with qualitative analysis. The juridical approach is used to examine the legal foundations of land registration digitalization, including Law No. 5 of 1960 on Basic Agrarian Principles, Government Regulation No. 24 of 1997 on Land Registration, and the Ministerial Regulation of ATR/BPN No. 1 of 2021 on Electronic Certificates. The empirical approach involves direct observation of service processes at the Land Office and interviews with employees and citizens utilizing digital services. The findings reveal that digitalization of land registration has generally improved the quality of services at the Land Office. Administrative processes have become faster, land data are stored more securely, and service transparency has increased, as the public can monitor the status of their registration online.